The Management of Acute Cholecystitis in Elderly Patients: Percutaneous Cholecystostomy versus Cholecystectomy - Günay, Yusuf; Emek, Ertan; Bircan, Hüseyin Yüce; Aktaş, Semra; Demirağ, Alp (Fırat University, 2013)
Objective: Treatment of acute cholecystitis in eldery patients still remains controversial. Because of advanced age that can influence surgical results, less invasive managements have been performed in this population. The goal of this study was to analyze the results of cholecystectomy versus percutaneous cholecystostomy for acute cholecystitis in elderly patients. Material and Method: Seventy four patients aged 65 years and older treated for acute cholecystitis were identified retrospectively from our medical records. Results: Of the 74 patients, 40 (54 %) underwent cholecystectomy, while 34 (46%) had a percutaneous cholecystostomy for AC as an initial treatment. The mean length of follow up was 28, 5±29, 3(1-35) months in percutaneous cholecystostomy and 12, 4±15 (1-42) months in cholecystectomy patients, respectively (p=0,0032). The success rate was significantly higher in cholecystectomy patients compared to percutaneous cholecystostomy patients (p=0,0210). Seventeen (50 %) patients who had PC subsequently underwent cholecystectomy. Readmission rates were higher in the percutaneous cholecystostomy group (p=0, 0848). There was no statistically significant difference in the patient survival rate between the two groups (p=0,1799). Conclusion: This study confirms that cholecystectomy is a more effective treatment than percutaneous cholecystostomy for acute cholecystitis in elderly patient who is fit for surgery.

Amaç: Yaşlılarda akut kolesistitin tedavisi hala tartışılan bir konudur. İleri yaşın cerrahi sonuçlar üzerindeki etkisi nedeni ile bu hastalarda daha az invaziv yöntemler bir seçenek olarak uygulanmaktadır. Bu çalışmada yaşlılarda akut kolesistit tedavisinde uygulanan kolesistektomi ile perkütan kolesistostominin sonuçları karşılaştırıldı. Gereç ve Yöntem: Akut kolesistit nedeni ile tedavi gören 65 yaş ve üzerindeki 74 hastanın dosyası geriye dönük olarak incelendi. Bulgular: Yetmiş dört hastadan, 40 (% 54) tanesi kolesistektomi ile 34 hasta ise perkütan kolesistostomi ile tedavi edildi. Ortalama takip süresi perkütan kolesistostomi grubunda 28,5±29,3 ( 1-35) ay, buna karşın kolesistektomi grubunda 12, 4±15 (1-42) aydı (p=0,0032). Tedavide başarı oranı kolesistektomi grubunda daha yüksekti ve bu farklılık istatistiksel olarak anlamlı idi (p=0,0210). Perkütan kolesistostomi yapılan hastaların on yedisi (%50) zamanla kolesistektomi ameliyatı oldu.Taburcu sonrası şikayetle hastaneye tekrar başvuru oranı perkütan kolesistostomi hastalarında daha yüksekti (p=0,0848). Her ne kadar perkütan kolesistostomi grubu hastalarında akut kolesistit'e bağlı ölüm oranı daha yüksek görülse de istatistiksel anlamda önemli bir farklılık görülmedi (p=0,1799). Sonuç: Bu çalışmada, yaşlılarda akut kolesistit tedavisinde kolesistektominin cerrahiye uygun hastalarda perkütan kolesistostomiden daha etkili bir tedavi yöntemi olduğunu gösterildi.
Yaşlılarda Akut Kolesistit Tedavisine Yaklaşım: Perkütan Kolesistostomi veya Kolesistektomi